A Feasibility Study on the Establishment of Vege Macaroons (Eatwork)in Glori Novaliches (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researchers conducted this research to challenge and apply the learnings of their chosen career and also a guide to know the possible outcome of their product called “Vege Macaroons”. The researchers think that they are able to use the vegetable as a main ingredient because it consumes a lot of nutrients that can improve our health. Filipinos in general ignore the potential health hazards posed by continuing to eat every unhealthy food. They ignore the vegetables because they do not like the texture and its taste. Everyone should know how important our health but being worried and hesitated can lost our appetite that is why the researchers tried to make different kinds of macaroons and make it more attractive to the eye so the customers will buy and try it. The researchers chose survey as a method in conducting the study because it is much easier to use the survey method in some studies because the information that you can gather from the respondents is easy to tabulate. The business called “EATWORK” is feasible based on the survey of the study that researchers made, the total layout and the minimal investment needed. The demand for the product rises due to fact that is a basic necessity for the customers and people to look for an affordable food particularly which that matches their budget and at the same time oversees good health among the consumers. Most of the customers are not familiar to the product so that the uniqueness is the key for our product to be sold. During these times most of us live by using social media so our product will easily be known by the use of social media. The Distributions shows that based on the findings, 40% of the respondents like the flavor of Okaroon and while the 40% likes the Takaroon. In terms of texture, 80% says that they like the chewy texture of coconut and the other 20% that says otherwise. 80% says that they like the chewy texture of vegetable that used in macaroons and the 20% says that they can't feel the chewy texture. There are a lot of Macaroons made with different kind of flavours and most of them are just coated with sweets. The Carrot Cake Macarooons (Lyn, 2013) has the same idea with our product and just like these macaroons it is made to satisfy the tummies and it is made to avoid any sickness that can be threat to everyone's life.
Keywords: vegetable, macaroons, feasibility study, BCP